Global hotspots and trends in research on preschool children’s motor development from 2012 to 2022: a bibliometric analysis - Wang, Jun-Wei; Qu, Sha; Zhu, Zhi-Cheng; Zhao, Xing; Song, Wen-Jing; Li, Xue; Chen, Wan-Di; Luo, Dong-Mei (Frontiers in Public Health, 2023)
Background: Motor development is a key aspects of human development throughout the life span and has received increasing scholarly attention in recent years. Nevertheless, exhaustive reviews of pertinent studies on this topic remain scant within the literature. Therefore, this bibliometric study was aimed at identifying motor development research hotspots and trends associated with preschool children during the period 2012–2022. Methods: CiteSpace 6.1.R4 was used to visualize and analyze general bibliometric characteristics, research hotspots, and trends through a review of 2,583 articles on the motor development of preschool children published between 2012 and 2022 and included in the Web of Science Core Collection. Results: Research on motor development in preschool children has entered a phase of rapid development, encompassing pediatrics, psychology, and public environmental occupational health. Moreover, a new trend of interdisciplinary cross-collaboration involving fields like sport sciences, molecular biology, and clinical medicine is evident. The top five frequently occurring keywords were physical activity (n = 489), performance (n = 319), intervention (n = 222), health (n = 196), and executive function (n = 165); The top five keywords in terms of centrality were academic achievement (0.22), low birth weight (0.16), association (0.14), brain (0.13), and cerebral palsy (0.13). Thirteen keyword clusters were produced from the log-likelihood ratio (Q = 0.74、S = 0.88), and five research topics within this field received focused attention in recent years. The keywords with the strongest citation bursts in last five years were developing country (S = 5.92), school-aged children (S = 5.86), middle-income country (S = 3.46), efficacy (S = 5.41), readiness (S = 3.21), motor proficiency (S = 3.6), and screen time (S = 3.3), indicating newly emerging research trends. Conclusion: Research hotspots and trends in preschool children’s motor development over the last decade were analyzed using bibliometric techniques. The results indicated that interventions involving fundamental movement skills, cognitive function, 24-hour movement behaviors, neurodevelopmental disorders, and health-related fitness were hot topics in the field of motor development. Emerging research trends generally center on school readiness, socioeconomic status, motor proficiency, and screen time.